Humanistic Synergy of Ki Hajar Dewantara and Paulo Freire in Educational Total Quality Management - Lili Hastuti; R Madhakomala (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze the synergy between the humanistic values of Ki Hajar Dewantara and Paulo Freire in the implementation of total quality management in educational institutions. The study employs a qualitative approach with a descriptive design, utilizing in depth interviews, participatory observations, and document analysis as data collection techniques. Data were analyzed through thematic analysis involving coding, categorization, and triangulation to ensure validity. The findings indicate that integrating Dewantara’s humanistic principles particularly the three education centers (family, school, and community) and leadership values with Freire’s dialogical pedagogy fosters participatory leadership, reflective learning, and active stakeholder involvement. This integration transforms total quality management from a predominantly administrative framework into a humanistic–transformative approach that emphasizes critical awareness, collaboration, and continuous improvement driven by collective consciousness. The study implies that a humanistic based total quality management model can enhance the effectiveness of educational quality management by strengthening character development, improving interpersonal relationships, and promoting sustainable quality culture. Practically, this approach provides strategic guidance for educational institutions to implement total quality management in a more inclusive, participatory, and socially relevant manner.